Innovative Leadership Approaches for Enhancing Digital Governance and Collaborative Networks in Public Administration - Fannur, Faiz; Sabaruddin, Ilham; Ramdhani, Nia (Journal Social Civilecial, 2023)
In particular, this research investigates competencies of leadership in public administration as a way of understanding how public administrators are positioning themselves in the current complex governance environment. Exploring leadership themes of digital media, communities, flexibility, and professionalism, the work employs a qualitative research method and outlines leadership priorities for practice and scholarship. Qualitative data were collected from interviews with public administrators to show how they use digital resources, cooperation between organizations, and response to new issues for enhancing public services. The study concludes that these models have the potential not only of increasing the efficiency of organizations but also transparency, accountability and citizens’ participation. Also, the study shows that despite adopting these strategies, public administrators experience some barriers including, resistance to change, poor digital literacy, and limited resources. In doing so, the current study adds to existing scholarship focusing on digital and collaborative leadership in responding to the ad hoc nature of leadership scholarship in the context of public administration. The present findings offer applied suggestions to public sector organizations such that they might develop better leadership and remain effective in managing future governance issues. This study stresses the centrality of leadership innovation as a driver of change in the public sector and provides an ideal background for subsequent research on combining adaptive, ethical leadership models in various governance environments.